Irish dual career athlete transitions into the US collegiate system - Marsh, F.; Sharp, L.-A.; Woods, D.; Paradis, K.; Pierce, S. (Psychology of Sport and Exercise, 2026)
Migrating dual career (DC) athletes may experience multiple transition events in sport and non-sport aspects of their lives. How successfully these are navigated can alter their career trajectory. This study combined holistic development and ecological approaches to explore Irish DC athlete perceptions of: (a) their transition to the US collegiate system throughout three transition phases and (b) changes in the support system in their transition environment. Through purposeful sampling, 11 participants were recruited from eight different sports (American Football N = 1; Basketball N = 1; Cross-country N = 2; Golf N = 2; Rowing N = 1; Tennis N = 1; Track & Field N = 1; Soccer N = 2; N = 4 females; N = 7 males; Mage = 20.04 years; SD = 1.88 years). A total of 36 individual semi-structured interviews, averaging 46.93 min (SD = 9.79 min), were conducted across three time points spanning 12 months. This rich experiential data was then examined using reflexive thematic analysis. Three first-order themes synthesized the Irish DC athlete transition journey through three phases, from scholarship dreams to reality; coping with the demands of being a student-athlete; and learning how to progress. Twelve second-order themes characterize salient elements of the DC athletes transition experiences through the three phases. Findings were examined adopting theoretical athlete transition models taking holistic, ecological and cultural perspectives. Findings informed a number of practical recommendations to assist successful athlete transitions which include improving: i) pre-transition phase preparation resources for DC athletes; ii) liaison between home and US collegiate coaches toward the DC athlete's holistic development; iii) DC athlete transition literacy; and iv) mental health and sport psychological professional support to those most likely experiencing crisis transition events.